Simulation of ecophysiological processes of growth in several annual crops (Pudoc, 1989)
The concepts underlying crop growth modelling, uses of such models and modelling techniques are discussed. The assimilation and use of carbon, morphological development and assimilate partitioning, transpiration and water uptake are explained in a whole-crop context and soil water balance processes considered. Dynamic summary models simulating these processes are presented and data sets for several annual agricultural crops are presented. Weather data generation is also discussed. The models can be used to evaluate new sites, crops or cultivars and husbandry and management techniques, and can assess the impact of year-to-year weather variability on the crop. The models are presented in an open rather than a black box manner allowing adaptation, modification and expansion (CAB abstract)